Development and Characterization of New Vegan Ice Cream from Tempeh Milk Enriched with Moringa Leaf Flour - Fransisca, Fransisca; Tri Kumala Dewi, Rike; Christie Harimas, Clarissa (Indonesian Food Science and Technology Journal, 2025)
Abstract— Vegan ice cream is among the currently trending plant-based products, but not all can meet nutritional needs, specifically protein and calcium, which are often found in milk. An effective strategy to address this problem is by adding moringa leaf flour (MLF) and tempeh milk, which are rich in protein and calcium. Therefore, this study aims to develop high-calcium vegan ice cream from tempeh milk enriched with MLF. The experimental method was divided into characterization of MLF and tempeh milk, physical characterization and sensory evaluation of ice cream with Check All That Apply (CATA) method, and chemical characterization for the most preferred recipe. The selected MLF concentrations included 4%, 5%, 6%, and 7%, where ice cream with a higher concentration had harder and stickier texture, as well as a higher melting time, and a smaller overrun value than counterparts developed using less MLF. Sensory evaluation was conducted with 50 untrained panelists, while the must-not-have properties of MLF ice cream were a dark green color, a solid appearance, a bitter taste and aftertaste, greeny flavor, and a hard texture. The most preferred formulation was ice cream containing 4% MLF, with characteristics such as 68.9% water, 0.59% ash, 2.38% protein, 5.43% fat, 22.70% carbohydrate, calcium 93.13 mg/100 g, and iron 1.02 mg/100 g. The best formula did not meet the regulation of calcium and protein source because of the sensory acceptance limitation.